2012
DOI: 10.1016/j.vetpar.2012.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic conservation of potentially immunogenic proteins among Brazilian isolates of Babesia bovis

Abstract: Bovine babesiosis caused by Babesia bovis remains an important constraint for the development of cattle industries worldwide. Effective control can be achieved by vaccination with live attenuated phenotypes of the parasite. However, these vaccines have a number of drawbacks, which justifies the search for better, safer vaccines. In recent years, a number of parasite proteins with immunogenic potential have been discovered. However, there is little information on the genetic conservation of these proteins among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
5
18
2
1
Order By: Relevance
“…Results on the genetic conservation between rap-1 sequences of B. bovis strains have also been reported elsewhere [33,34]. Nevertheless, our isolates formed a monophyletic grouping clearly distinct from that of other published B. bovis strains, and this suggested the presence of micro-heterogeneities among the rap-1 sequences within B. bovis species.…”
Section: Resultssupporting
confidence: 82%
“…Results on the genetic conservation between rap-1 sequences of B. bovis strains have also been reported elsewhere [33,34]. Nevertheless, our isolates formed a monophyletic grouping clearly distinct from that of other published B. bovis strains, and this suggested the presence of micro-heterogeneities among the rap-1 sequences within B. bovis species.…”
Section: Resultssupporting
confidence: 82%
“…When Brazilian B . bovis isolates were analyzed in a recent study, the authors found that several genes, including MSA-2c, were highly conserved and shared high sequence identity with the genes from T2Bo [18]. In the present study, however, the MSA-1 gene sequences were found to separate into three different clades.…”
Section: Discussioncontrasting
confidence: 59%
“…bovis among cattle populations in Thailand, Brazil and Ghana has been previously reported [1, 7, 18]. A recent study based on AMA-1, ACS-1, RAP-1, TRAP, pO and MSA-2c genes found that the Brazilian B .…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, these observations suggest that the levels of genetic diversity in the B. bovis MSA genes are similar in the cattle and water buffaloes of Vietnam. The MSA-2c gene is diverse in Australia (Berens et al, 2005), Sri Lanka (Sivakumar et al, 2013b), the Philippines (Tattiyapong et al, 2014), and Israel (Molad et al, 2014), whereas this gene is conserved in Mongolia (Altangeral et al, 2012) and Brazil (Ramos et al, 2012). In addition, the sequences isolated in Argentina, Mexico, and USA shared high similarities, suggesting that the MSA-2c from distant geographical locations may also sometimes be conserved (Dominguez et al, 2010;Florin-Christensen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%